The Crucial Role of PPARγ-Egr-1-Pro-Inflammatory Mediators Axis in IgG Immune Complex-Induced Acute Lung Injury - Yan, Chunguang; Chen, Jing; Ding, Yue; Zhou, Zetian; Li, Bingyu; Deng, Chunmin; Yuan, Dong; Zhang, Qi; Wang, Ximo (Frontiers in Immunology, 2021)
Background The ligand-activated transcription factor peroxisome proliferator-activated receptor (PPAR) γ plays crucial roles in diverse biological processes including cellular metabolism, differentiation, development, and immune response. However, during IgG immune complex (IgG-IC)-induced acute lung inflammation, its expression and function in the pulmonary tissue remains unknown. Objectives The study is designed to determine the effect of PPARγ on IgG-IC-triggered acute lung inflammation, and the underlying mechanisms, which might provide theoretical basis for therapy of acute lung inflammation. Setting Department of Pathogenic Biology and Immunology, Medical School of Southeast University Subjects Mice with down-regulated/up-regulated PPARγ activity or down-regulation of Early growth response protein 1 (Egr-1) expression, and the corresponding controls. Interventions Acute lung inflammation is induced in the mice by airway deposition of IgG-IC. Activation of PPARγ is achieved by using its agonist Rosiglitazone or adenoviral vectors that could mediate overexpression of PPARγ. PPARγ activity is suppressed by application of its antagonist GW9662 or shRNA. Egr-1 expression is down-regulated by using the gene specific shRNA. Measures and Main Results We find that during IgG-IC-induced acute lung inflammation, PPARγ expression at both RNA and protein levels is repressed, which is consistent with the results obtained from macrophages treated with IgG-IC. Furthermore, both in vivo and in vitro data show that PPARγ activation reduces IgG-IC-mediated pro-inflammatory mediators’ production, thereby alleviating lung injury. In terms of mechanism, we observe that the generation of Egr-1 elicited by IgG-IC is inhibited by PPARγ. As an important transcription factor, Egr-1 transcription is substantially increased by IgG-IC in both in vivo and in vitro studies, leading to augmented protein expression, thus amplifying IgG-IC-triggered expressions of inflammatory factors via association with their promoters. Conclusion During IgG-IC-stimulated acute lung inflammation, PPARγ activation can relieve the inflammatory response by suppressing the expression of its downstream target Egr-1 that directly binds to the promoter regions of several inflammation-associated genes. Therefore, regulation of PPARγ-Egr-1-pro-inflammatory mediators axis by PPARγ agonist Rosiglitazone may represent a novel strategy for blockade of acute lung injury.